2016
DOI: 10.1159/000446111
|View full text |Cite
|
Sign up to set email alerts
|

Do the Anti-Müllerian Hormone Levels of Adolescents with Polycystic Ovary Syndrome, Those Who Are at Risk for Developing Polycystic Ovary Syndrome, and Those Who Exhibit Isolated Oligomenorrhea Differ from Those of Adolescents with Normal Menstrual Cycles?

Abstract: Background/Aims: We aimed to investigate whether the anti-Müllerian hormone (AMH) levels in adolescents with polycystic ovary syndrome (PCOS), PCOS risk, and isolated oligomenorrhea (OM) were different than in adolescents with a normal/regular menstrual cycle (NMC). Methods: The diagnosis of PCOS was based on the 2012 Amsterdam [European Society of Human Reproduction and Embryology/American Society for Reproductive Medicine (ESHRE/ASRM)] criteria. The PCOS group consisted of cases meeting 3 diagnostic criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Our cross-sectional observation of a significant difference in serum AMH concentrations between obese girls with PCOS vs. without PCOS supports and advances previous findings in the pediatric literature (15-20). However, most of the pediatric literature on AMH is in lean girls or combined non-obese and obese PCOS girls (16-20), without particular focus in obese girls.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our cross-sectional observation of a significant difference in serum AMH concentrations between obese girls with PCOS vs. without PCOS supports and advances previous findings in the pediatric literature (15-20). However, most of the pediatric literature on AMH is in lean girls or combined non-obese and obese PCOS girls (16-20), without particular focus in obese girls.…”
Section: Discussionsupporting
confidence: 90%
“…However, most of the pediatric literature on AMH is in lean girls or combined non-obese and obese PCOS girls (16-20), without particular focus in obese girls. Our data show that obese girls with PCOS have ~50% higher serum AMH levels compared with obese girls without PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estrogens are transformed from androgens by aromatase. Experimental studies in animal models revealed that anti-Muellerian hormone (AMH), which is increased in PCOS (34), inhibits the FSH-dependent aromatase in granulosa cells (35). Studies in women with PCOS reported negative associations between AMH and estradiol concentrations (36).…”
Section: Discussionmentioning
confidence: 99%